2018
DOI: 10.1007/s11096-018-0666-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and readiness for medication therapy management among community pharmacists in Lebanon

Abstract: Background To follow international standards, the Lebanese Order of Pharmacists would like to start to implement the medication therapy management in community pharmacies. Objective The objective of this study is to evaluate community pharmacists' knowledge of and readiness for medication therapy management. Setting Community pharmacists from all Lebanese regions. Method A cross-sectional observational descriptive study was conducted. Pharmacists at their workplace completed self-administered anonymous standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…Several studies highlighted the need for appropriate physical spaces for medication and disease state management services in community pharmacies. 28,29 Some pharmacies stopped providing medication management service due to the lack of private space. 27…”
Section: Integration Of Mtm Within the Pharmacy Workflowmentioning
confidence: 99%
“…Several studies highlighted the need for appropriate physical spaces for medication and disease state management services in community pharmacies. 28,29 Some pharmacies stopped providing medication management service due to the lack of private space. 27…”
Section: Integration Of Mtm Within the Pharmacy Workflowmentioning
confidence: 99%
“…This was actually highlighted in the present study, whereby most participants reported they did not find personnel working at dispensaries qualified to deal with their health. Trusting a pharmacist and recognising his or her indispensable role in the healthcare team is a basic requirement, especially considering that pharmacists may be the first healthcare professional to directly interact with the public in addition to being available for at least 8 h/day without prior appointment . Although most respondents (90%) reported that community pharmacists are important members in the healthcare system, and trusted their knowledge, 30% of participants still thought that a pharmacist only sells medication and has no other role.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient clinical knowledge is one of the main barrier in providing appropriate interventions. 15,16 The provision of minor ailment services as well as other expanded pharmacist-roles (e.g., medication therapy management, immunization) in developed countries has been successful 17,18 yet these practices and the knowledge of Filipino pharmacists on these roles have not been investigated. The majority (77%) of Filipino pharmacists practicing in a community setting, 19 their experience and knowledge on the management of minor ailments remain undocumented.…”
Section: Introductionmentioning
confidence: 99%